A PHONEMIC ANALYSIS BETWEEN ENGLISH AND INDONESIAN IN “HEAVEN” SONG - Anggraini, Leli; Sinaga, Kelly; Sirait, Febrianto; Barus, Reulina Arita; Siahaan, Veronika Febryanti; Sitanggang, Anita (Transpublika Publisher, 2022)
This study compares and contrasts the phonetic systems of English and Indonesian in the lyrics to the song